The relationship between the profile the mother & development of maternal behavior during rooming-in among primipara in selected hospital in Paranaque/ Angel C. Elane, Ma. Lycar R. Goingo, Lissel B. Goneo, and Luceila T. Mariano - Elane, Arncel C.; Goingo, Ma. Lycar R.; Goneo, Lissel B.; Mariano, Luceila T. (Paranaque City; Olivarez College, 2009)
This study focuses on the relationship between the profile of the mother and the development of maternal behavior during rooming-in which comprises mothers who gave birth for the first time. This study aimed to answer two questions, namely: What is the demographic profile of Primipara according to Age, Civil status, Socio-economic, and Educational Attainment; and, what is the relationship of age, Civil Status, Socio-economic and Educational attainment through development of maternal behavior. The Table 11 shows that the majority of the respondents answer agrees with positive outcome that they experience changes and development on their behavior, indicating that they have positive attitude and behavior towards the mother and the baby and their interaction or bonding during rooming-in. Health Promotion Model served as the theoretical framework being utilized in this study. The respondents were selected purposively and surveys were done with the aid of survey guides. In analyzing the responses of the maternal behavior among primipara mothers through their demographic profile, the group was able to determine: (1) the majority of the respondents agreed that the most of the mother has change and develop their behavior, (2) In the age category, the majority of the age group that has their first baby is in 1922. At that age group, most of the respondents are housewives and the least are the students; (3) and according to their educational attainment, the respondents are mostly high school graduates and it indicates that early exposure to unwanted pregnancy and peer pressure, lack of knowledge and awareness and curiosity.
Undergraduate Thesis